IMPACT OF THE IMPROVEMENT OF THE NATIONAL CURRENCY SYSTEM ON THE IMPORT-EXPORT AUTHORITY (World Bulletin of Management and Law, 2023)
In this article, import-export relations are the main factors of the development of foreign economic relations of the country. It is well known that today trade surplus helps economic growth. More exports mean more output from factories and production facilities, as well as more people employed to keep those factories running
Keywords: Export; joint-stock companies; trade surplus; import